Pengaruh Model Pembelajaran Novick Berbantuan LKPD Terhadap Kemampuan Kognitif Peserta Didik - Nurhayati, Iis; Yusandika, Ajo Dian; Basyar, Syarifudin; Anjelinar, Yuwana (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to determine wether there is an influence of the learning model Novick assist LKPD on the cognitive abilities of students in class VIII of SMP IT Baitun Nur Central Lampung on motion and style material. The method used is a quantitative method in the form of quasi experimental design with nonequivalent control group design. To determine the cognitive abilities of student and the control class, the Mann Whitney Test was conducted on the SPSS 23.0 program. The result of data analysis show sig values. (2-tailed) of 0.00 which means the value of sig. (2-tailed) less then 0.05, which means that the average posttest of the control class is not the same as the average posttest of the experimental class. Thus, it is accepted or there is a difference in the average score of the posttest cognitive abilities of students in the experimental class higher than the average posttest cognitive abilities of student in the control class. Abstrak:Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh model pembelajaran Novick berbantuan LKPD terhadap kemampuan kognitif peserta didik kelas VIII SMP IT Baitun Nur Punggur Lampung Tengah pada materi gerak dan gaya.Metode yang digunakan adalah metode kuantitatif berupa penelitian quasi experimental design dengan desain nonequivalent control group design. Untuk mengetahui kemampuan kognitif peserta didik kelas eksperimen dan kelas kontrol dilakukan uji Mann Whitney Test pada program SPSS 23.0. Hasil analisis data menunjukkan nilai sig. (2-tailed)sebesar 0,00 yang berarti nilai sig. (2-tailed) kurang dari 0,05 yang artinya rata-rata posttest kelas kontrol tidak sama dengan rata-rata posttest kelas eksperimen. Sehingga,  diterima atau terdapat perbedaan nilai rata-rata posttest kemampuan kognitif peserta didik pada kelas eksperimen lebih tinggi dari rata-rata posttest kemampuan kognitif peserta didik pada kelas kontrol.